PENGARUH NET PROFIT MARGIN, NON PERFORMING LOAN DAN CAPITAL ADEQUACY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Hutasoit, Putri Lamsari; Sinaga, Cindia; Marbun, Rimtauli; Sembiring, Samuel Abel Tanta; Sinaga, Jholant Bringg Luck Amelia (Aksara Public, 2019)
This study aims to examine and analyze the Effect of Net Profit Margin, Non Performing Loans and Capital Adequacy Ratio on Banking Company Stock Prices Listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. The research approach used in this study is a quantitative approach, the type of research is descriptive analysis, the nature of research is causal nature, the data collection method is the documentation method, the analysis technique used is multiple linear regression analysis, and the population in this study are 43 banking companies listed on the Indonesia Stock Exchange (IDX). And the sample used was 26 companies. From this population there are 26 companies selected using the purposive sampling method. In this study multiple linear regression analysis techniques. Based on the results of simultaneous hypothesis testing, Net Pofit Margin, Non Performing Loans and Capital Adequacy Ratios have a significant effect on Stock Prices, with the test results the coefficient of determination is 28% of the Variable Stock Price variable which can be explained by the variable Net Pofit Margin, Non Performing Loans and Capital The remaining Adequacy Ratio72% is explained by other variables not examined in this study. While based on the results of partial hypothesis testing on Net Profit Margin, Capital Adequacy Ratio doesn’t significant to stock prices and Non Performing Loans have a positve and significant effect on stock prices.